Considering a spectrum of necropolitical harms: geographies of asylum in Nottingham, Calais and beyond - Peters, Freya (2024)
This thesis explores the experiences of violence for refugees and asylum seekers in Nottingham and Calais and beyond. I situate these experiences of violence in relation to Mbembe’s (2003) postcolonial theory of necropolitics. I argue that necropolitics is a suitable framework to view this violence because the experiences of refugees and asylum seekers involve harms which can be considered either outright killing or being kept “alive but in a state of injury” (Mbembe, 2003:21). These harms occur as an expression of necropower wielded by the sovereign in ways which reflect colonial power relations and hierarchical conceptions of race. I argue that there is value in considering necropolitics as a spectrum of harms which range in temporality and visibility (Mayblin, 2019a). The contribution that this thesis makes is that I argue there is a need to consider how necropolitical harms across this spectrum combine over the course of a lifetime rather than viewing them each in isolation.